Synthesis of 13,14-dehydroprostacyclin methyl ester: a potent inhibitor of platelet aggregation. - Fried, J (1977)
The structure of the most recently discovered, biologically highly active prostaglandin, PGI2 or prostacyclin, is correctly predicted on biogenetic grounds, and a general synthesis starting with prostaglandins of the F2alpha series is reported. Starting with the biologically active 13,14-dehydro-PGF2alpha, the synthesis involves formation of a 5-bromo-6,9alpha-epoxy derivative, followed by esterification and dehydrobromination of the methyl ester to form the prostacyclin structure. The stereochemistry at C-5 and C-6 of all reported products is assigned on the basis of experimental findings and mechanistic reasoning. 13,14-Dehydroprostacyclin methyl ester is considerably more stable at pH 7.5 than prostacyclin. It inhibits platelet aggregation induced by a variety of agents and causes an increase in renal blood flow in the dog at nanomolar levels.